Penerapan Peningkatan Pengetahuan Aksi Bullying di Lingkungan Sekolah UPT SDN 060917 Medan - Malida Putri; Tiara Fany Chintia Silitonga (ABDISOSHUM: Jurnal Pengabdian Masyarakat Bidang Sosial dan Humaniora, 2023)
The rise of bullying in the community is very troubling, especially in the school environment. In this case bullying at school can have very serious effects both in the short and long term for the victims. In the short term Bullying can lead to feelings of insecurity, fear of going to school, feeling isolated, feelings of low selfesteem, depression or even suffering from stress which can end in suicide for the victim. Meanwhile, in the long term, victims of bullying can experience emotional and behavioral problems. Therefore, to prevent bullying from escalating, assistance is needed to increase students' knowledge about the negative effects of bullying and invite students to make changes. The process of providing this assistance will be carried out through PKL 1 activities by creating a Mini Project. Activities will be carried out using the casework method which consists of the Engagement Intake Contract, Assessment, Planning, Intervention, Evaluation, and finally Termination. The focus of the client's problem solving process is to educate students about bullying through verbal explanations, animated videos, making posters, and taking real action in the field. The final result of this program was declared successful, it can be seen from the significant changes in students, namely starting to reduce the attitude of ridicule, getting more compact, and increasing students' knowledge about bullying.